Efficacy and safety of mechanical thrombectomy in distal medium middle cerebral artery occlusion ischemic stroke patients on low-dose aspirin - Salim, Hamza; Yedavalli, Vivek; Milhem, Fathi; Musmar, Basel; Adeeb, Nimer; Daraghma, Motaz; El Naamani, Kareem; Henninger, Nils; Sundararajan, Sri Hari; Kühn, Anna Luisa; Khalife, Jane; Ghozy, Sherief; et al. (International journal of stroke, 2025)
Background: Acute ischemic stroke (AIS) from distal medium vessel occlusion (DMVO) presents unique treatment challenges. Mechanical thrombectomy (MT) is emerging as a viable option for these patients, yet the role of pre-stroke aspirin treatment is unclear. This study evaluates the impact of pre-stroke low-dose aspirin on outcomes in DMVO patients undergoing MT. - Methods: We conducted a multinational, multicenter, propensity score-weighted analysis within the Multicenter Analysis of primary Distal medium vessel occlusions: effect of Mechanical Thrombectomy (MAD-MT) registry. Patients with AIS due to DMVO, treated with MT, were included. We compared outcomes between patients on pre-stroke low-dose aspirin (75-100 mg) and those not on antiplatelet therapy. The primary outcome was functional independence at 90 days (modified Rankin Scale (mRS), 0-2). Secondary outcomes included excellent functional outcome at 90 days (mRS, 0-1), mortality, and day 1 post-MT National Institutes of Health Stroke Scale (NIHSS) score. Safety outcomes focused on hemorrhagic complications, including symptomatic intracerebral hemorrhage (sICH). - Results: Among 1354 patients, 150 were on pre-stroke low-dose aspirin. After applying inverse probability of treatment weighting (IPTW), aspirin use was associated with significantly better functional outcomes (mRS, 0-2: odds ratio (OR) = 1.89, 95% confidence interval (CI) = 1.14 to 3.12) and lower 90-day mortality (OR = 0.56, 95% CI = 0.32 to 1.00). The aspirin group had lower NIHSS scores on day 1 (β = −1.5, 95% CI = −2.8 to −0.27). The sICH rate was not significantly different between the groups (OR = 0.92, 95% CI = 0.60 to 1.43). - Conclusions: Pre-stroke low-dose aspirin was associated with improved functional outcomes and reduced mortality in patients with DMVO undergoing MT, without a significant increase in sICH. These findings suggest that low-dose aspirin may be safe and associated with more frequent excellent outcomes for this patient population. Further prospective studies are needed to validate these results and assess long-term outcomes.
Gesehen am 12.09.2025